Clinical, pathological, and biological characterization of Richter syndrome developing after ibrutinib treatment for relapsed chronic lymphocytic leukemia. Issue 3 (27th February 2018) - Innocenti, Idanna; Rossi, Davide; Trapè, Giulio; Autore, Francesco; Larocca, Luigi Maria; Gomes, Vincenzo; Cerri, Michaela; Falcucci, Paolo; Sica, Simona; Gaidano, Gianluca; Laurenti, Luca
Abstract: Richter syndrome, a transformation of chronic lymphocytic leukemia (CLL) into a diffuse large B‐cell lymphoma, is a rare complication of patients treated with chemo‐immunotherapy. Richter syndrome might be both clonally related or unrelated to the underlying CLL and often showed mutations of the TP53 and NOTCH1 genes. Recently, ibrutinib was approved for patients with relapsed/refractory CLL or for untreated CLL patients with del 17p or TP53 mutation. The clinical picture, pathology, and genetics of Richter transformation after IBR treatment are largely unknown. Here, we report 2 cases of Richter transformation after Ibrutinib treatment. As just reported by previous report, Richter syndrome developing after ibrutinib therapy lacked resistance mutations of the BTK and PLCG2 genes, which are clonally related to the pre‐existent CLL phase representing transformation from CLL. Richter syndrome after ibrutinib seems to have some peculiar clinical findings as the bone marrow predilection, severe hypercalcemia, and a more aggressive outcome.